Análisis del riesgo y estabilidad de taludes en la sede circunvalar de la Universidad Antonio Nariño - Gomez Coca, Yuri Tatiana; Roldan Alvis, Diana Silvia (Universidad Antonio Nariño, 2024)
In view of the imminent risks currently presented by landslides and their innumerable consequences, the purpose of the research project is to perform a slope stability analysis in Block 4 of the Antonio Nariño University's Circunvalar campus by means of limit equilibrium methods (Fellenius, Bishop and Janbú methods), which allow determining the safety factor and correlating it with SLIDE modeling, under static and pseudo-static conditions.